2003
DOI: 10.1159/000072074
|View full text |Cite
|
Sign up to set email alerts
|

Different Proliferative and Apoptotic Activity in Peripheral versus Central Parts of Human Uterine Leiomyomas

Abstract: Objective: To determine whether there are differences in proliferative and apoptotic activity and in expression of sex steroid receptors between central and peripheral parts of human uterine leiomyomas in different menstrual cycle phases. Methods: Biopsy specimens of the myometrium and peripheral and central parts of uterine leiomyomas were obtained from 15 women in the proliferative phase and 8 women in the secretory phase. Mitotic cells were detected by immunohistochemical staining for Ki67. Apoptotic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
1
6
0
3
Order By: Relevance
“…Also, other studies comparing estrogen receptor protein expression in leiomyomas from women in the proliferative and secretory phases have shown that ER was expressed at lower levels during the secretory phase. This supports the concept that progesterone may be decreasing the levels of ERα, thereby making less receptor available for phosphorylation [3, 22, 43]. …”
Section: Discussionsupporting
confidence: 83%
“…Also, other studies comparing estrogen receptor protein expression in leiomyomas from women in the proliferative and secretory phases have shown that ER was expressed at lower levels during the secretory phase. This supports the concept that progesterone may be decreasing the levels of ERα, thereby making less receptor available for phosphorylation [3, 22, 43]. …”
Section: Discussionsupporting
confidence: 83%
“…The reason that the xenograft tissues obtained by LAM and TAH failed to grow after implantation might be due to mechanical tissue damage induced by the device and long-term blood occlusion of feeder arteries before hysterectomy, respectively. In regard to the size of the myoma and the sites of tissue harvesting, although no statistically significant difference was found in the capacity for growth between the central site and the marginal site in myomas, larger-sized myomas have cells in the marginal sites that are highly mitogenically active, which results in more outer growth 16 , 17 .…”
Section: Discussionmentioning
confidence: 92%
“…Pertinently, peripheral parts of leiomyomas have been shown to have a higher turnover of cells compared with the central parts30. In addition to pAkt, the tumour suppressor LKB1 also regulates the mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%